Preliminary Study of the Entrepreneurial Soul (Enterpreneur) of High School Students in Scientific Chemistry Learning with a Scientific Approach (Universitas Negeri Semarang, 2020)
The results of this research study with descriptive qualitative methods aim to analyze the findings related to the entrepreneurial spirit of high school students. The subjects in this study were 69 students of class XI involving 2 state high schools in Semarang in the academic year 2018/2019. Data collection is done by observation, questionnaires, and documentation. The results showed that 64.71% in SMA X had an entrepreneurial spirit with strong criteria and 35.29% with very strong criteria. In state high school Y 2.86% have an entrepreneurial spirit with weak criteria, 65.71% strong criteria and 31.43% very strong criteria. High school students tend to have an entrepreneurial spirit with strong criteria. But after being analyzed, the lowest score on the entrepreneurial spirit is the aspect of confidence. Various supports in learning can be done to improve the quality of learning and produce students who have good self-confidence. Steps that need to be taken include improving the method or model of learning and using teaching materials that support the growth of the entrepreneurial spirit, especially in the aspect of self-confidence.